DOES MICROFINANCE MODEL DETERMINE THE EFFECTIVENESS OF MICROFINANCE INTERVENTION IN ENHANCING MICROENTERPRISE PERFORMANCE? EVIDENCE FROM BANK RAKYAT INDONESIA - Weni Hawariyuni; Salina Hj Kassim (Share: Jurnal Ekonomi dan Keuangan Islam, 2016)
This study aims to investigate the effectiveness of different microfinance model in enhancing the performance of microenterprises in terms of income, fixed assets, and household expenditures. By focusing on the case of Bank Rakyat Indonesia, one of the most successful commercial microfinance providers in the world, two types of microfinance products, namely KUPEDES and KUR are being compared. The KUPEDES is original product of BRI Unit, while the KUR is a micro-product subsidized by the Indonesian government. Based on the experience of BRI Unit in Medan city, Indonesia, we assess the impact of microfinance intervention on 400 clients. The findings demonstrated that KUPEDES as original microproduct is more successful compared to KUR product in enhancing the performance of microenterprise through income, fixed assets, and household expenditures as successful indicators. =========================================== Kajian ini bertujuan untuk menginvestigasi keefektifan beragam model pendanaan mikro dalam meningkatkan performa usaha kecil dari segi pemasukan, aset tetap, dan belanja rumah tangga. Dengan fokus pada kasus Bank Rakyat Indonesia, salah satu pemberi dana mikro paling berhasil di dunia, kajian ini membandingkan dua macam produk pendanaan mikro, yaitu KUPEDES dan KUR. KUPEDES adalah produk original BRI sementara KUR adalah sebuah produk mikro yang disubsisdi oleh pemerintah Indonesia. Berdasarkan pengalaman BRI cabang Medan, Indonesia, penulis menilai dampak campur tangan pendanaan mikro terhadap 400 orang klien. Hasil penelitian menunjukkan bahwa KUPEDES sebagai produk mikro original dinilai lebih berhasil dibandingkan dengan KUR dalam meningkatkan performa usaha kecil dengan indikator kesuksesan: pemasukan, asset tetap, dan belanja rumah tangga.